Turning Audiovisual Archives Into Scientific Assets - Jähnichen, Gisa (Journal of Knowledge Management Practice, 2011)
University practice requires a high level output of publications and other evidence of scholarly productivity by its researchers and lecturers. Listed categories of efficient evidence show clearly which kind of output is accepted: namely those listed in ‘so called’ collections of ‘citation indexed’ journals such as Thompson Reuters’ ISI web of knowledge, Scopus and Springer Link. Archived items of audiovisual material including metadata and further supplementary descriptions are not to be found in these sources and it seem they will never be; neither will journals connected to this kind of ‘rare disciplines’ that use audiovisual materials and metadata. My paper focuses on ways of knowledge communication in this field and on some reasons of their actual status embedded into the competitive thinking of institutionalised higher education. What role can audiovisual archives with their collections play in this context? A vision can emerge from the findings, which should be brought into a discussion that reaches beyond archive and university walls.
Keywords: knowledge management; Audiovisual archives; Multi-format knowledge distribution; Humanities; Social sciences; Rare disciplines; Local languages